"Always on and always on them": Portable radios and the creation of the mobile media experience. (September 2016) - Cohen, Mary Morley
This article investigates the early history of portable radio in the United States from 1920 through 1954. As the first mobile electronic device, the portable radio reveals important information about how the mobile media experience has developed over time. Portable radio afforded several new experiences that are relevant to today's media landscape: it allowed users to create customizable, mobile media environments that they could take with them wherever they went; it redefined the radio listening context by allowing users to bring their preferred forms of entertainment with them when travelling to unfamiliar places; and it facilitated more continuous media consumption habits. This interdisciplinary essay combines close textual analysis of historical newspaper articles and advertisements, which are viewed through the lens of a range of media theories. The goal is to uncover some of the complex effects of early mobile media and to lay the groundwork for future in-depth studies of mobile media history.